Comparison of the use of titanium–zirconium alloy and titanium alloy in dental implants: A systematic review and meta-analysis - Cruz, Ronaldo Silva [UNESP]; Araujo Lemos, Cleidiel Aparecido [UNESP]; Fernandes Oliveira, Hiskell Francine [UNESP]; De Souza Batista, Victor Eduardo; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP] (American Academy of Implant Dentistry, 2018)
The aim of this study was to compare the values of bone-implant contact (BIC) and removal torque (RTQ) reported in different animal studies for titanium–zirconium (TiZr) and titanium (Ti) dental implants. This review has been registered at PROSPERO under number CRD42016047745. We undertook an electronic search for data published up until November 2017 using the PubMed/Medline, Embase, and The Cochrane Library databases. Eligibility criteria included in vivo studies, comparisons between Ti and TiZr implants in the same study, and studies published in English that evaluated BIC and RTQ. After inclusion criteria, 8 studies were assessed for eligibility. Of the 8 studies, 7 analyzed BIC outcome and 3 analyzed RTQ outcome. Among such studies, 6 studies were considered for meta-analysis of quantitative for BIC and 2 studies for RTQ. There was no significant difference for BIC analysis (P ¼ .89; random ration [RR]: 0.21; 95% confidence interval [CI]: 3.14 to 2.72). The heterogeneity of the primary outcome studies was considered low (7.19; P ¼ .21; I 2 : 30%). However, the RTQ analysis showed different results favoring the TiZr dental implants (P ¼ .001; RR: 23.62; 95%CI: 9.15 to 38.10). Low heterogeneity was observed for RTQ (v 2 : 1.25; P ¼ .26; I 2 : 20%). Within the limitations of this study, there was no difference between TiZr and Ti alloys implants in terms of BIC. However, TiZr implants had higher RTQ than Ti alloys.
Keywords: Dental alloy; Dental implants; Osseointegration; Titanium; Zirconium